On Analysis of Single Solution for a Class of BVP with Generalized Caputo-Katugampola Fractional Derivative - Bekri, Zouaoui; Samei, Mohammad Esmael; Erturk, Vedat Suat; Haque, Salma; Mlaiki, Nabil (New York Business Global LLC, 2025)
In this paper, we endeavor to simulate the existence of a single solution for a BVP for Caputo-Katugampola fractional derivative in the manner theorem of contraction of Banach. We extrapolate similar examples to interpret the conclusions reached.
Samei, Mohammad Esmael/0000-0002-5450-3127; Samei, Mohammad Esmael/0000-0002-5450-3127
Keywords: Banach Contraction Theorem; Caputo-Katugampola Fractional Derivative; BVP; Uniqueness and Existence